An Examination of Asian American Officers in State and Federal Law Enforcement. (22nd November 2022) - Yu, Helen H.
Abstract: The increasing concerns about anti-Asian hate crimes, attacks, and xenophobic violence as a result of the COVID-19 outbreak, coupled with the recent killing spree (March 16, 2021) targeting the Asian community in Georgia, has emphasized the scant research on Asian Americans in policing. This article represents the second half of a 2-part series detailing the employment figures of Asian officers in the United States. Using the latest data on race and ethnicity compiled by both the Law Enforcement Management and Administrative Statistics (LEMAS) survey and the Census of Federal Law Enforcement Officers (CFLEO), this study examines all the state law enforcement agencies, as well as the major federal law enforcement agencies employing at least 100 officers (or agents), to investigate Asian diversity across state and federal policing. Findings reveal that Asian Americans are underrepresented in nearly every state and federal law enforcement agency in the country, with the exception of two state police organizations and three federal law enforcement components.